2005
DOI: 10.5551/jat.12.143
|View full text |Cite
|
Sign up to set email alerts
|

Non-HDL Cholesterol as a Predictor of Carotid Atherosclerosis in the Elderly

Abstract: The aim of the present study was to evaluate sclerotic lesions of the common carotid artery by ultrasonography in 921 in-patients aged 65 years and older (77 ± ± ± ± ± 7 years) and investigate whether lipid levels were associated with carotid atherosclerosis. In men, an increased risk for carotid atherosclerosis was associated with increased levels of low-density lipoprotein cholesterol (LDL-C) and non-high-density lipoprotein cholesterol (non-HDL-C). Compared to men with the lowest tertile of LDL-C levels (< … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Moreover, with respect to carotid atherosclerosis, which is a useful tool to predict the likelihood of cardiovascular disease 6,7) and is related to many atherosclerotic risk factors 8,9) , an association between CRP levels and the presence of carotid plaques has been shown in univariate analysis in a prospective survey conducted in the general community (age range, 40 to 79 years) 10) or in healthy middle-aged women with a history of smoking 11) . However, Tracy et al 12) failed to demonstrate a relationship between CRP and carotid arterial intima-media thickness (IMT) and plaque.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, with respect to carotid atherosclerosis, which is a useful tool to predict the likelihood of cardiovascular disease 6,7) and is related to many atherosclerotic risk factors 8,9) , an association between CRP levels and the presence of carotid plaques has been shown in univariate analysis in a prospective survey conducted in the general community (age range, 40 to 79 years) 10) or in healthy middle-aged women with a history of smoking 11) . However, Tracy et al 12) failed to demonstrate a relationship between CRP and carotid arterial intima-media thickness (IMT) and plaque.…”
Section: Introductionmentioning
confidence: 99%
“…The dyslipidemias arise from physiological changes that result in serum values above or below the desirable for CT (total cholesterol), LDL-C (LDL cholesterol), TG (triglycerides), relations CT/HDL-C and LDL-C/HDL-C and for the fraction non-HDL-C (non-HDL cholesterol), but mainly when HDL-C (HDL cholesterol) is below the desirable [18]- [20]. HDL-C is one of the most promising indicators to determine risk of atherosclerotic cardiovascular disease [21]. There is an increased risk with the growth of LDL-C, non-HDL-C, CT, and the biggest ratio CT/HDL-C has a positive linear relationship with Atherosclerotic cardiovascular disease, as well as LDL-C, especially in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increased risk with the growth of LDL-C, non-HDL-C, CT, and the biggest ratio CT/HDL-C has a positive linear relationship with Atherosclerotic cardiovascular disease, as well as LDL-C, especially in elderly patients. The increase in the rates of CT, LDL-C, non-HDL-C, apoB, TC/HDL-C, LDL-C/HDL-C, and apoB/apoA-I are associated with the presence of atherosclerotic plaque [21] [22], but highlighting the ratio CT/HDL-C. By de way, the non-HDL-C could be usefulness as a risk marker of cardiovascular disease [23], and non-HDL-C would be more related to apoB than with the LDL-C, having the same predictive value that these lipoproteins. Therefore, the increased level of HDL-C is associated with the decrease in the thickening of the intima of carotid average in patients with type 2 DM and atherosclerosis [24].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that non-HDL cholesterol is better than LDL cholesterol in its predictive power of cardiovascular diseases, indicating that VLDL cholesterol could contribute to CVD 12) . Non-HDL cholesterol is also a useful marker in a variety of subpopulations: men, the elderly, and patients with high-risk diseases such as diabetes and end-stage renal disease [13][14][15][16] . Our current clinical data from patients with type b hyperlipidemia also support the usefulness of non-HDL cholesterol ( Table 1).…”
Section: Predictive Power Of Non-hdl Cholesterolmentioning
confidence: 99%